EFEKTIVITAS PEMBATASAN USIA PERKAWINAN BERDASARKAN UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN - Musyarrofa Rahmawati; Hanif Nur Widhiyanti; Warkum Sumitro (Universitas Negeri Malang, 2018)
This article described the effectiveness of limiting the age of marriage based on Act No.1 of 1974 about marriage. The method used empirical juridical or sociological juridical in Probolinggo Regency. The informants in this study were principles, teachers of Counseling Guid- ance, Heads of Religious Affairs Offices in Probolinggo District, and dropout students who under- age marriages. The results of the study showed that restrictions on marriage age have not been effective in the implementation domain. This fact showed from a large number of underage marriages conducted among the public. Factors causing marriage under age were: (1) community culture, matchmaking, (2) relationships that were too close in dating, (3) pregnancy outside marriage.DOI: http://dx.doi.org/10.17977/um019v3i12018p100